CO2 storage in coal to enhance coalbed methane recovery: a review of field experiments in China. Issue 5 (26th April 2018) - Pan, Zhejun; Ye, Jianping; Zhou, Fubao; Tan, Yuling; Connell, Luke D.; Fan, Jingjing
ABSTRACT: Coal reservoirs especially deep unminable coal reservoirs, are viable geological target formations for CO2 storage to mitigate greenhouse gas emissions. An advantage of this process is that a large amount of CO2 can be stored at relatively low pressure, thereby reducing the cost of pumping and injection. Other advantages include the use of existing well infrastructure for CO2 injection and to undertake enhanced recovery of coalbed methane (ECBM), both of which partially offset storage costs. However, ECBM faces difficulties such as low initial injectivity and further permeability loss during injection. Although expensive to perform, ECBM field experiments are essential to bridge laboratory study and large-scale implementation. China is one of the few countries that have performed ECBM field experiments, testing a variety of different geological conditions and injection technologies. These projects began more than a decade ago and have provided valuable experience and knowledge. In this article, we review past and current CO2 ECBM field trials in China and compare with others performed around the world to benefit ECBM research and inform future projects. Key aspects of the ECBM field projects reviewed include the main properties of target coal seams, well technologies, injection programmes, monitoring techniques and key findings.